How grit enhances physical exercise in college students: mediating roles of personal growth initiative and self-efficacy - Hu, Chang; Zhang, Wen; Huang, Wenying; Jin, Chanjuan (Frontiers in Psychology, 2025)
ObjectiveThis study aims to investigate the impact of Grit on physical exercise (PE) among college students and explore the underlying mechanisms, particularly focusing on the mediating roles of personal growth initiative (PGI) and self-efficacy (SE). It also examines how these psychological factors interact to influence physical activity, offering insights for educational interventions.MethodsA survey was conducted among 2,559 college students using the Short Grit Scale (Grit-S), the Personal Growth Initiative Scale-II (PGIS-II), the General Self-Efficacy Scale (GSE), and a single-item measure of physical exercise (PE).Results(1) Grit, PGI, SE, and PE were significantly positively correlated with each other. (2) PGI and SE played significant mediating roles in the relationship between Grit and PE. Specifically, three mediating pathways were identified: the independent mediating effect of PGI, the independent mediating effect of SE, and the chain mediating effect of PGI and SE.ConclusionGrit significantly influences PE among college students through the mediating effects of PGI and SE. Enhancing these psychological factors can be an effective strategy for increasing PE participation. This study provides a theoretical basis for developing targeted interventions to promote PE among college students.